Isotopic Insights into Dietary Life History, Social Status, and Food Sharing in American Samoa. Issue 2 (20th February 2019) - Eerkens, Jelmer W.; Bartelink, Eric J.; Bartel, Julianna; Johnson, Phillip R.
Abstract : We test the antiquity of a dietary life history model on Tutuila, American Samoa. Stable carbon and nitrogen isotopes in serial, age-adjusted samples of first and third molars reveal isotopic biographies of 16 individuals from five late Holocene (200–1100 RCYBP) sites. Combining this with bone collagen from a larger sample of individuals, we document a patterned dietary life history on the island. Between ages zero and two years, infants show elevated δ 15 N values, consistent with a diet rich in breast milk. In early childhood (two–10 years), individuals shift to a diet with higher δ 13 C values, suggesting greater marine protein intake. Around age 10 years, males shift to a more terrestrially focused diet, while females retain a higher marine signature. After 20 years of age, males and females are more similar in diet, with a greater contribution from terrestrial resources. We argue that these shifts reflect diet-marked social transitions in life histories, especially social status and eating order within households, as predicted from the ethnographic model. When contextualized with other archaeological data, such as mortuary patterns and social organization, the isotopic biographic approach facilitates examination of diet-linked social transitions of individuals as they aged within ancient societies. Abstract : En este artículo ponemos a prueba la antigüedad de un modelo etnográfico sobre la historia de vida dietética y la organización de las unidades domésticas en la Isla de Tutuila, localizada en la Samoa Americana. Analizamos los isótopos estables de carbono y nitrógeno en muestras seriadas ajustadas a la edad del primer y tercer molar. Estas representan las biografías isotópicas de 16 individuos procedentes de 5 sitios arqueológicos del Holoceno tardío (200–1100 aP). Combinando esta información con muestras adicionales de colágeno óseo, extraídas de un mayor número de individuos, pudimos documentar el patrón dietético de individuos en la isla. La mayoría de los infantes entre 0 y 2 años de edad muestra niveles elevados de δ 15 N, en consonancia con una dieta rica en leche materna. En la niñez temprana (2–10 años) hay un cambio hacia niveles más elevados de δ 13 C, lo que sugiere un consumo mayor de proteínas marinas. Alrededor de los 10 años de edad, los individuos de sexo masculino cambian a una dieta basada en recursos terrestres, mientras que aquellos de sexo femenino retienen valores elevados de δ 13 C asociados con el consumo de proteínas marinas. Después de aproximadamente 20 años de edad, ambos sexos muestran más similitud en el patrón dietético. Argumentamos que los cambios reflejan las transiciones sociales en las historias de vida de los individuos. Cuando se contextualiza con otros datos arqueológicos, como patrones funerarios y organización social, el enfoque biográfico isotópico facilita el examen de las transiciones sociales ligadas a la dieta a lo largo de la vida de los individuos en sociedades antiguas.